Obstacles to using authentic evaluation strategies in teaching natural sciences from the point of view of science teachers in the both primary and intermediate stages in the city of Makkah Al-Mukarramah - Al-Otaibi, Mukhlid Saad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the obstacles facing science teachers in both primary and intermediate stages in the city of Makkah Al-Mukarramah when using authentic evaluation strategies, and revealing the extent to which there are differences in these obstacles in the light of some variables. The study followed the descriptive survey method. The study tool consisted of a questionnaire of four axes: the educational environment, the academic courses, the science teacher, and the students. The questionnaire was applied to a stratified random sample of (428) science teachers from primary and middle schools in the city of Makkah. The results showed that science teachers face high obstacles when using authentic evaluation strategies as a whole, as well as in the axes: the educational environment, the science teacher, and students; While the obstacles were moderate in the academic courses. The results also showed that there were statistically significant differences in the total degree of obstacles and in the axes of the educational environment, and the science teacher, due to the difference in the academic stage in favor of primary school teachers. There were also differences in the total degree and in the sub-axes, except the academic courses, due to the difference in the number of years of experience, these differences were in favor of teachers with experience less than ten years in the total degree and in the axes of the educational environment, and the science teacher, while the differences were in favor of teachers with experience of 10 years or more in the axis of obstacles related to students, also, differences were found in the four sub-axes due to the difference in the academic qualification, in favor of postgraduate in the two axes of the educational environment and the science teacher, and in favor of the bachelor in the two axes of the academic courses, and the students. There were also differences in the total score and in the axes: the educational environment, the science teacher, and the students, due to the difference in the number of training courses in favor of teachers who did not receive training courses, except for the students’ axis where the differences were in favor of teachers who had one to three courses. The study recommended several recommendations, the most important of which is the design of planned training programs in light of the training needs of science teachers, and the development of a simplified guide for students about the authentic evaluation.